Exploring the potency of Streptomyces koyangensis strain SHP 9-3 isolated from the soil of Enggano Island (Indonesia) as an antibacterial source (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pahira DSJ, Damayanti E, Lisdiyanti P, Mustofa, Hertiani T. 2023. Exploring the potency of Streptomyces koyangensis strain SHP 9-3 isolated from the soil of Enggano Island (Indonesia) as an antibacterial source. Biodiversitas 24: 1460-1466. Streptomyces is a Gram-positive bacterium with the potential a produce beneficial antimicrobials. This study aimed to determine the antimicrobial activity, morphological characteristics, cytotoxicity, and chemical profile of S. koyangensis SHP 9-3. This bacterium was isolated from Enggano Island, Indonesia, and the morphological characteristics were determined using a Scanning Electron Microscope (SEM). Cultivation was conducted in the International Streptomyces Project (ISP-2) media using baffled flasks and a shaker incubator. The secondary metabolites were conducted on the extract against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans by a twofold dilution method. Concurrently, cytotoxicity testing was done on Vero cells. The extract’s chemical profile was analyzed using LC-MS/MS. The results showed a prominent antibacterial activity as the extract inhibited the growth of S. aureus and C. albicans at 7.81 µg/mL. However, a growth inhibition against E. coli was observed at 250 µg/mL and P. aeruginosa at 31.25 µg/mL. The cytotoxic test showed the IC50 value on Vero cells was 5,015 µg/mL, indicating that the extract was nontoxic against Vero cells. The chemical profile of the extract by LC-MS/MS revealed the presence of five major components, i.e., cyclo (Pro-Val) (C10H16N2O2), kuraramine (C12H18N2O2), 1,4-diphenyl-1-pentanone (C17H18O), (3S,4S)-4-amino-3-hydroxy-6-methyl heptanoic acid (C21H42N2O7), and 2-ethyl-8-methyl-2,8-diazaspiro (4,5) decane-1,3-dione (C11H18N2O2).
Keywords: Antifungal, antimicrobial, LC-MS/MS, secondary metabolites, Streptomyces